PREVALENCE OF MASTITIS AND ANALYSIS OF RISK FACTORS AMONG DAIRY BUFFALOES IN UBAY, BOHOL, PHILIPPINES - Tapdasan, Emerson Pilongo; Balala, Lotis M; Olana, Kenny Oriel A; Bajenting, Gundolino P; Salces, Caro Bojo (Journal of Agriculture and Technology Management; Vol 21 No 1 (2018): Journal of Agriculture and Technology Management (JATM) Volume 21 January - June 2018 Issue, 2018)
Mastitis is an economically important disease of intensive dairy farming worldwide. Detection using reliable tests is important for its management and control. The purpose of this study was to estimate the prevalence and analyze the risk factors for mastitis in the dairy farm of Philippine Carabao Center at Ubay Stock Farm (PCC-USF) in Ubay, Bohol. Data on animal demographics, reproduction status, daily milk yield and Somatic Cell Count (SCC) were obtained from PCC-USF records. Data were analyzed using the Chi-square test and Odds Ratio (OR) at 5% level of significance. Univariate analysis was used to assess the association between putative risk factors & elevated SCC (>200,000 cells/mL). The proportion of mastitis using SCC was 17.9%. The prevalence was lower than those reported in other studies. Specifically, mastitis prevalence was higher in the following groups of buffaloes: American Murrah, 6-7 years old, 1-90 days of lactation, non-pregnant and ≥2 parities (P>0.05). None of the factors investigated were associated with mastitis prevalence which could be attributed to the small sample size of the study.  Future studies should be carried out involving large sample sizes and bacteriological examinations to determine animal-level risk factors and implicating microorganisms, respectively.